A study of certain aspects of the Mount Coke Missionary Institution - Walker, James Andrew (Rhodes University, Faculty of Divinity, Department of Divinity, 1955)
In searching for information concerning the chain of stations that William Shaw established from the Eastern Frontier of the Cape Colony towards Natal, I found that I had to consult many books. Many sources of information have recently come to light and this had to be analysed as well. In this work much had to be included that did not directly refer to Mount Coke, but it is relevant in that it affected the history of the Mission, and the effect of the Mission on the community as a whole. When histories of all the stations are written the incidents should show up in the right perspective.
Keywords: Shaw, William, 1798-1872; Missions -- South Africa -- Eastern Cape; Missionaries -- South Africa -- Eastern Cape